The Quality of Zephyr Board Made from Oil Palm Brunch (Eleais guenensis Jacq.) - Lusita Wardani; Muhammad Y Massijaya; Yusuf Sudo Hadi; Wayan Darmawan (Masyarakat Peneliti Kayu Indonesia, 2013)
The objective of this research was to evaluate the physical, mechanical and durability properties of zephyr board made from oil palm petiole. Urea formaldehyde (UF), phenol formaldehyde (PF) and isocyanate (IC) resins were used to bind zephyrs. Board size produced was (300x300x12) mm3, and target density of zephyr board was set at 0.80 g cm-3. The temperature and pressure of hot pressing were set at 120 °C and 25 kg cm-2 for 20 min. The result showed that physical and mechanical properties of zephyr board fulfilled JIS A 5908-2003. All board density in this experiment did not reach the density target. The moisture content of zephyr board bonded with IC resin was the lowest compared to zephyr board bonded with UF and PF resins. Over all the mechanical properties of zephyr board bonded with UF resin showed the best result in term of modulus of rupture (MOR), modulus of elasticity (MOE), internal bond (IB), and screw resistant (SR) parameters compared with zephyr board bonded with PF and Isocyanate resins. Zephyr board was classified into I-II class for strength class and I-IV class for resistance against dry and subterranean termites, attack respectively.Key words: durability, mechanical properties, physical properties, resin type, zephyr board